The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1091/mbc.e17-01-0018
|View full text |Cite
|
Sign up to set email alerts
|

An endosomal syntaxin and the AP-3 complex are required for formation and maturation of candidate lysosome-related secretory organelles (mucocysts) inTetrahymena thermophila

Abstract: Lysosome-related organelles (LROs) are secretory organelles formed by convergence between secretory and endosomal trafficking pathways. In Tetrahymena, secretory vesicles that resemble dense core granules are a new class of LROs whose synthesis depends on a conserved syntaxin required for heterotypic fusion and AP-3 for maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 99 publications
4
36
0
Order By: Relevance
“…Significantly, mucocysts are not multivesicular, unlike Apicomplexan rhoptries. However, the delivery to mucocysts of Cth3p and Grt/Igr proteins, but not the Grl proteins, requires the sortilin/VPS10 receptor, Sor4p, as well as an endosomal SNARE (Soluble NSF attachment protein receptor), Stx7l1p (Syntaxin 7-like) [47,48]. These results suggested that extrusomes in ciliates may depend on LRO-related mechanisms that bear fundamental similarities with those used in apicomplexans.…”
Section: Lro Formation Involves Cytoplasmic and Membrane Proteins Incmentioning
confidence: 94%
“…Significantly, mucocysts are not multivesicular, unlike Apicomplexan rhoptries. However, the delivery to mucocysts of Cth3p and Grt/Igr proteins, but not the Grl proteins, requires the sortilin/VPS10 receptor, Sor4p, as well as an endosomal SNARE (Soluble NSF attachment protein receptor), Stx7l1p (Syntaxin 7-like) [47,48]. These results suggested that extrusomes in ciliates may depend on LRO-related mechanisms that bear fundamental similarities with those used in apicomplexans.…”
Section: Lro Formation Involves Cytoplasmic and Membrane Proteins Incmentioning
confidence: 94%
“…Tetrahymena transformants were generated and selected after biolistic transformation as previously described (Kaur et al, 2017;Sparvoli et al, 2018). Transformants were serially transferred 6x/week in increasing concentrations of drug and decreasing concentrations of CdCl 2 (up to 2 mg/ml of paromomycin and 0.1 μg/ml CdCl 2 ; up to 18-21 μg/ml of cycloheximide and 1 μg/ml CdCl 2 ; up to 90 μg/ml of blasticidin and 0.1 μg/ml…”
Section: Biolistic Transformationmentioning
confidence: 99%
“…The expression of Rab7 was induced by adding 1 μg/ml CdCl 2 to the S medium. Cells were immobilized in thin 3% low melting agarose gel pads, as described previously (Kaur et al, 2017), and imaged within 15 minutes. Z stack images (12 stacks along the z axis at 0.5 μm intervals) and time-lapse videos (30 frames at 1.24 sec interval for mNeon-tagged Vps8 paralogs; 200 frames at 0.17 sec/interval for Vps8c-mNeon/mCherry-Rab7) were collected at room temperature with a Marianas Yokogawa type spinning disk inverted confocal microscope, 100X oil with NA=1.45, equipped with two photometrics Evolve back-thinned EM-CCD cameras, with Slidebook6 software (Zeiss, Intelligent Imaging Innovations, Denver, CO).…”
Section: Live Cell Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a subunit of the AP3 complex and a syntaxin in the STX7 subfamily. Subsequent functional analysis of these genes showed that they are both essential for mucocyst formation, providing the best evidence to date that mucocysts are lysosome-related organelles [31]. The CDH report for this CTH3 query is attached as Supplementary File 4.…”
Section: Illustrative Examplesmentioning
confidence: 99%